UJI AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL BIJI JAMBU BOL (Syzygium malaccense L) DENGAN METODE DPPH (2,2-Diphenyl-1-picrylhidrazil) - Siti Juariah; Larasari Putri; Rosa Devitria (LPPM Universitas Abdurrab, 2022)
Antioxidants are compounds that can overcome the negative effects of oxidants in the body. Antioxidants have an important role for the health of human body because they can slow or prevent oxidation that involves free radicals. Free radicals will cause several degenerative diseases. Based on the source, antioxidants are divided into two groups, they are natural antioxidants and synthetic antioxidants. Seeds guava bol is one of the plants that used in traditional medicine which has the potential as a natural antioxidant. The purpose of this study was to determine the antioxidant activity of the methanol extract of seeds guava bol through the IC50 value. The method used in this study is the 2,2-Diphenyl-1-Picrylhidrazil (DPPH) method, which is a method of measuring antioxidants that is fast, simple, accurate and inexpensive. The results showed that the IC50 value was 1.627 ppm. From the IC50 value obtained, it is known that the methanol extract of guava seeds has strong antioxidant activity to fight free radicals.